Adsorption behaviour of bulgur. (15th March 2016) - Erbaş, Mustafa; Aykın, Elif; Arslan, Sultan; Durak, Atike N.
Highlights: Bulgur is a nutritive, traditional and long-term storable wheat product. The adsorption isotherms of bulgur were the type II isotherm and multilayer. The adsorption capacity of bulgur decreased with increasing particle size. Bulgur must be stored below 70% relative humidity and 10% moisture content. Abstract: The aim of this research was to determine the adsorption behaviour of bulgur. Three different particle sizes (2 < coarse < 3.5, 1.6 < medium < 3.0, 0.5 < fine < 2.0 mm) of bulgur, purchased from market, were kept in nine different equilibrium levels of relative humidity (8.2–97.3%) at 20, 30 and 40 °C. The data obtained were evaluated using BET (Brunauer–Emmett–Teller) and GAB (Guggenheim, Anderson and deBoer) sorption equations. The equilibrium moisture content of bulgur increased both with decreasing temperature and bulgur size. The constants m 0 and C of BET and GAB equations were determined to be between 2.54 and 5.03 g water per 100 g of dry matter and 4.96–16.57, respectively. Constant k was between 0.85 and 0.93, and GAB equation was determined to fit very well for bulgur adsorption, because of % E values lower than 10%. Bulgur must be stored below 70% relative humidity and with less than 10 g water per 100 g of dry mater.